Lymphocytic Hypophysitis Presenting as Bilateral Abducens Nerve Palsy: A Case Report. (3rd March 2020) - Waldie, Anna M.; Lau, Oliver; Gild, Matti; Little, Nicholas S.; Brewer, Janice; Thieben, Mark J.; Clifton-Bligh, Roderick; Smith, James E. H.
ABSTRACT: Lymphocytic hypophysitis (LYH) is a neuroendocrine disorder characterised by autoimmune inflammation of the pituitary gland with varying degrees of pituitary dysfunction, visual field defects and ocular motility disturbance. The authors report an interesting case of a 50-year-old woman presenting with intermittent bilateral abduction deficits. Neuroimaging and histopathological findings are presented. To the authors' knowledge, this is the first report of recurrent horizontal binocular diplopia and complete bilateral internal carotid artery occlusion in association with LYH.